CH3NH3PbI3: precise structural consequences of water absorption at ambient conditions. Issue 5 (16th September 2016) - Arakcheeva, Alla; Chernyshov, Dmitry; Spina, Massimo; Forró, László; Horváth, Endre
Abstract : Structure, symmetry and hydrogen bonds have been determined for pristine and aged tetragonal CH3 NH3 PbI3 crystals upon H2 O absorption from air at room temperature. Single‐crystal X‐ray diffraction data obtained on a synchrotron light source was used for the study. H2 O insertion into the structure changes hydrogen bonds and, consequently, the space group from I 422 (pristine crystal) to P 42 21 2 (aged crystal). Abstract : The crystal structure of the pristine (I) and aged (II) crystals of CH3 NH3 PbI3 (hereafter MAPbI3 ) hybrid organic–inorganic lead iodide has been studied at 293 K with high‐precision single‐crystal X‐ray diffraction using a synchrotron light source. We show that (I) and (II) are characterized by an identical tetragonal unit cell but different space groups: I 422 for (I) and P 42 21 2 for (II). Both space groups are subgroups of I 4/ mcm, which is widely used for MAPbI3 . The main difference between (I) and (II) comes from the difference in hydrogen bonds between the MA + cation and the PbI3 framework which is the direct consequence of H2 O insertion in the aged crystal (II).